Cegah Stunting Melalui Pendampingan Ibu Balita di Posyandu RW 01 Kelurahan Kampung Bandar, Kecamatan Senapelan, Pekanbaru - Imelda Fitri; Syahda Elsavira; Jihan Bela Islami; Dwi Jayanti; Sausan Sabira; Arguna Lenggogeni; Dandy Sayundra; Juliana Rosmasari; Livia Amelia Sari; Vira Aulia Putri; Yoanita Nabila; Oktavia Veronika; Putri Desinta; Ovi Wiranda; Raihana Satira; Yulia Afrina (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2024)
The problem health of stunting needs serious attention. This activity aims to assist and increase the knowledge of mothers at posyandu picking happy days in achieving the goal of preventing stunting in children in order to achieve a state of complete physical and mental well being and free from chronic diseases. The method used in this activity is in the form of health counseling using a tool in the form of posters. Participants were given material on stunting and continued with a question and answer session, where there was filling out of knowledge questionnaires before dan after health counseling. The activity participants, namely mothers at the posyandu, picked happy days as many as people where the activity lasted 100 minutes. All mother of child were able to understand well to prevent stunting by increase in the average value of knowledge from 5.4 to 7.8 (pre-test and post-test results) of 2.5 points. It is hoped that PKM activities can be carried out continuously, so that prevent of stunting can early detect.